2016
DOI: 10.1016/j.electacta.2016.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-carbon-coated LiMn0.4Fe0.6PO4 nanopowders with excellent high rate and low temperature performances for lithium-ion batteries

Abstract: Ascorbic acid acts as both an antioxidant and a surfactant to form organic groups (first carbon source) on the surface of as-solvothermal products, in which the-OH (or H 2 O) groups of glucose (second carbon source) are closely bonded to the surface to form a uniform adsorption layer. Uniform mixed-carbon-coated LiMn 0.4 Fe 0.6 PO 4 nanopowders are formed after calcination, which demonstrate excellent electrochemical performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Meanwhile, we note that one additional cathodic peak (3.6 V) appears for both electrodes. This would arise from the incomplete Li intercalation in MnPO 4 engendering the formation of Mn 3+ ‐containing FePO 4 , which can be intercalated by Li at ≈3.6 V versus Li/Li + to form some intermediate LiFePO 4 . Besides, two peak currents ( I p ) from anodic and cathodic processes of LFMP‐IGF are larger than those of LFMP‐TGF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, we note that one additional cathodic peak (3.6 V) appears for both electrodes. This would arise from the incomplete Li intercalation in MnPO 4 engendering the formation of Mn 3+ ‐containing FePO 4 , which can be intercalated by Li at ≈3.6 V versus Li/Li + to form some intermediate LiFePO 4 . Besides, two peak currents ( I p ) from anodic and cathodic processes of LFMP‐IGF are larger than those of LFMP‐TGF.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the elemental mapping images (Figure g–j and Figure S2: Supporting Information) indicate that LFMP NPs were uniformly embedded within the rGO skeleton, and Mn has been doped into the Fe site in LiFe 0.7 Mn 0.3 PO 4 crystals. The higher voltage given by the redox couple Mn 2+ /Mn 3+ would contribute to increase the energy density of the electrode . In addition, the cross‐section of LFMP‐IGF is shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Chen et al reported LiMn 0.4 Fe 0.6 PO 4 /C nanopowders with excellent high-rate and low-temperature performance, which delivered 128 mAh g À1 at ah igh currentr ate of 20 Ca nd 107 mAh g À1 at À20 8C. [22] Chen et al produced LiMn 0.6 Fe 0.4 PO 4 /C microspheres using oxalates and as pray-drying method, which showed ar eversible capacity of about 152 mAh g À1 after 500 cycles at 1C, indicative of outstanding cycle stability. [23] Sun et al synthesized LiMn 0.5 Fe 0.5 PO 4 /C microsized spheres using coprecipitated phosphate as precursor,w hich retained 85 %o ft heir capacity at 55 8C.…”
Section: Introductionmentioning
confidence: 99%